Efektivitas penerapan kerangka kerja manajemen risiko dalam operasi pembiayaan perbankan syariah - Cahyati, Ratih Nur (Maliki Interdisciplinary Journal, 2024)
Sharia banking cannot avoid risk, so it is necessary to implement effective risk management in every banking institution. The purpose of risk management is to support the achievement of company goals. Therefore, this research was conducted to analyze the implementation of financing risk management at Bank Syariah ABC. Using descriptive qualitative research methods and the data obtained comes from secondary data. This research found that Bank Syariah ABC has succeeded in implementing risk management effectively in financing management by establishing special work units, namely the Financing Risk Analysis Work Unit and the Risk Management Department.